China's Belt and Road Initiative Changing the Rules of Globalization (Palgrave Studies of Internationalization in Emerging Markets,, 2018)
Since the introduction of the One Belt, One Road initiative (OBOR), first proposed in late 2013, international scholars have begun to study this new policy and its implications in the global age. While OBOR provides new opportunities for China in terms of regional cooperation and global development, many also raise concerns about China's intentions of using economic means to achieve strategic and foreign policy objectives. Hailing from the West and the East, the authors reflect on the wide-ranging impacts of OBOR on specific countries, regions, economic policies, and geopolitical considerations. Including both theoretical research and empirical studies that explore opportunities and challenges related to OBOR, this edited volume will allow readers to gain a more comprehensive understanding of this ambitious undertaking and its long-term impact on the rest of the world.